Challenges and recommendations for embracing digital tools for one health surveillance in LMICs: Viewpoints from a special session of 17th ISVEE - Thang Nguyen-Tien; Unger, Fred; Yano, T.; Mutua, Florence K.; Cook, Elizabeth A.J.; Hu Suk Lee; Bett, Bernard K.; Hung Nguyen-Viet (Elsevier, 2025)
The adoption of digital tools presents a critical opportunity to enhance One Health initiatives in low- and middle-income countries (LMICs). At the 17th International Symposium of Veterinary Epidemiology and Economics (ISVEE17), a special session explored the role of Information and Communication Technology (ICT) applications in addressing zoonoses, animal diseases, food safety, and antimicrobial resistance (AMR) in Asia and Africa countries. This paper highlights key insights from that session, indicating the barriers and opportunities for ICT implementation and expansion including user engagement and incentives, data quality and standardization, infrastructure, evidence and policy advocacy, capacity building, network and knowledge exchange, sustainability. The necessity of co-design, infrastructure investment, applications integration, interoperability and collaboration among international and national organizations, cross-sectoral and interdisciplinary approaches, continuous training and evidence-based policy support and sustainable funding models are crucial for building effective, inclusive, and scalable ICT-driven solutions.